2003
DOI: 10.1007/s00122-002-1145-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a unique genomic clone located 5′ upstream of the Oshsp16.9B gene on chromosome 1 in rice (Oryza sativa L. cv Tainung No. 67)

Abstract: Small heat-shock proteins (sHSP) are the most abundant heat stress-induced proteins in plants. In rice, there are at least seven members of class-I sHSP. A 1.6-kb DNA fragment was isolated from the EcoRI-digested rice genomic library probed with the cDNA pTS1 encoding a 16.9-kDa class-I sHSP. This fragment was composed of 365-bp tandem direct repeats (DRs) and 441-bp near perfect long terminal inverted repeats (LTIRs). The DRs contain 123-bp regions with 99% nucleotide identity to the 5' coding region of the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…A similar expression profile of all sHSP-CI genes at a lower level was suggested by ethanol, H 2 O 2 and CuCl 2 treatments (Guan et al, 2004 (Guan et al, 2003(Guan et al, , 2004. Chang et al (2007), for the first time, reported a fulllength cDNA clone for a class II sHSP, isolated from riceetiolated seedlings heat shocked at 41 o C for 2 h. The coding sequence consists of 501 bp, and the clone encodes a protein of 18.0 kDa.…”
Section: Hsp60 Familysupporting
confidence: 57%
See 1 more Smart Citation
“…A similar expression profile of all sHSP-CI genes at a lower level was suggested by ethanol, H 2 O 2 and CuCl 2 treatments (Guan et al, 2004 (Guan et al, 2003(Guan et al, , 2004. Chang et al (2007), for the first time, reported a fulllength cDNA clone for a class II sHSP, isolated from riceetiolated seedlings heat shocked at 41 o C for 2 h. The coding sequence consists of 501 bp, and the clone encodes a protein of 18.0 kDa.…”
Section: Hsp60 Familysupporting
confidence: 57%
“…The DRs contain 123-bp regions with 99% nucleotide identity to the 5' coding region of the Oshsp16.9B gene. This fragment in proximity 5'-upstream of the OsHSP16.9B gene that was mapped on chromosome 1 with other two class-I sHSP genes, OsHSP16.9A and OsSHP16.9 C. Comparative analysis of the nucleotide sequences of class-I sHSP genes clustered on chromosome 1 showed that only the promoter region of OsHSP16.9B was different (Guan et al, 2003).…”
Section: Shsp Promotersmentioning
confidence: 89%
“…In our previous studies, we identified seven sHSP-CI genes in rice using rice Oshsp16.9A as a screening probe Lee et al, 1995;Chang et al, 2001;Guan et al, 2003). These genes were located on the rice chromosomes by RFLP using gene-specific 3¢-UTRs.…”
Section: Rice Shsp-ci Gene Family Contains Nine Membersmentioning
confidence: 99%
“…Because of the distinct abundance and complexity of sHSP-CI in rice, much research has concentrated on the identification of sHSP-CI genes in our laboratory (Tseng et al, 1993;Tzeng et al, 1993;Lee et al, 1995;Chang et al, 2001;Guan et al, 2003). In this report, we identified and characterized nine members of the rice sHSP-CI gene family on chromosome 1 and 3 and examined during seed maturation and the effects of various stresses including HS, Aze, As, Cd, and ethanol on expression profiles of these genes in etiolated seedlings.…”
Section: Introductionmentioning
confidence: 98%
“…Chromosomal mapping was conducted according to the method of (Guan et al 2003). On the basis of 196 RFLP loci, molecular linkage map was developed and data were scored as described by Wang et al (1998).…”
Section: Chromosome Mappingmentioning
confidence: 99%